Orthodoxy, Activism, and the Salience of Religion - Bahr, Howard M. (Journal for the scientific study of religion, 1971)
It is proposed that previous studies of the relationship between orthodoxy and social activism have yielded inconsistent findings because a critical mediating variable, salience or perceived importance of religion, usually has been neglected. Findings from a survey of 1,300 students at Washington State University support the hypothesized role of salience as a mediating variable. Relationship between orthodoxy and church activism emerges only for the high salience subsamples. The apparent utility of the orthodoxy-salience-activism model for bringing coherence to previously inconsistent findings seems to argue for more widespread use of salience as a control variable in studies of the concomitants and consequences of religiosity.